2018
DOI: 10.1021/acs.iecr.8b00430
|View full text |Cite
|
Sign up to set email alerts
|

Selection between Separation Alternatives: Membrane Flash Index (MFLI)

Abstract: Chemical process design is a creative step of engineers that should be supported by different computer-aided design tools. Such tools should be simple and easy to use because process synthesis often means the investigation of a huge number of alternatives. During the design of the separation of liquid mixtures, among many others, distillation and pervaporation are usually simultaneously considered because pervaporation is frequently considered as an alternative to distillation. To easily compare the efficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…MFLI was also used to evaluate the PV membranes' capabilities in liquid separation compared to traditional distillation. It can be seen that the graphene/PVA MMMs prepared in this work exhibited comparable or even higher MFLI values compared with other PVA-based MMMs reported in the literature, which indicated that pervaporation with these MMMs possessed better separation efficiency over flash distillation [44,45]. According to the results, it was presumed that graphene intercalated with an appropriate number of oxygen-containing groups might be a good choice to prepare PVA-based MMMs for ethanol dehydration, which would combine the advantages of GR's high interlayer diffusion selectivity and GO's high permeation properties and open a door to achieve both high permeation flux and the separation factor of MMMs by tuning the microstructure of graphene.…”
Section: Comparison Of Pv Performance Of Pva-based Mmmssupporting
confidence: 58%
See 3 more Smart Citations
“…MFLI was also used to evaluate the PV membranes' capabilities in liquid separation compared to traditional distillation. It can be seen that the graphene/PVA MMMs prepared in this work exhibited comparable or even higher MFLI values compared with other PVA-based MMMs reported in the literature, which indicated that pervaporation with these MMMs possessed better separation efficiency over flash distillation [44,45]. According to the results, it was presumed that graphene intercalated with an appropriate number of oxygen-containing groups might be a good choice to prepare PVA-based MMMs for ethanol dehydration, which would combine the advantages of GR's high interlayer diffusion selectivity and GO's high permeation properties and open a door to achieve both high permeation flux and the separation factor of MMMs by tuning the microstructure of graphene.…”
Section: Comparison Of Pv Performance Of Pva-based Mmmssupporting
confidence: 58%
“…GR showed a strong diffraction peak at 2θ = 26.55 • , and the corresponding interplanar spacing of GR was only 0.33 nm due to the strong π-π interaction between GR lamellae [41]. The GR interplanar spacing (0.33 nm) was exactly in between the kinetic diameters of ethanol and water molecules, which was 0.43 nm and 0.26 nm, respectively [45]. This might facilitate the selective permeation of water molecules.…”
Section: Crystal Structures Of Pva-based Mmmsmentioning
confidence: 96%
See 2 more Smart Citations
“…In steady-state operations, the combinations of two phases are permanent and in equilibrium. The liquid and vapor phases are fed into a decanter (phase separator) where they are treated separately. , …”
Section: Introductionmentioning
confidence: 99%